Franz Liszt under the Light of Progress The Idea of Mehrdeutigkeit as Aesthetic Paradigm in the Piano Compositions between the B minor Sonata and the Bagatelle sans tonalité - Bettoni, Willy (Voces, 2021)
The idea of progress became increasingly relevant during the 19th century, eventually instigating a paradigm shift. This transformation facilitated not only the emergence of numerous philosophical and literary trends, but also engendered new perspectives in music theory. The composer Franz Liszt was also influenced by the spirit of the epoch. This study's analysis of his piano compositions from the Sonata in B Minor to the Bagatelle sans tonalité shows how he shaped and adapted his musical language and aesthetic thinking on the basis of what he called the 'ideal of the time'.